Rusia: política exterior hacia Estados Unidos sobre arsenales nucleares - Ortega, Martha (Revista Mexicana de Política Exterior, 2022)
Ortega begins her essay by taking a brief look at the foreign policy adopted by the Soviet Union and later Russia toward the United States on the issue of nuclear arsenals. The discovery of nuclear fission just before the outbreak of World War II opened up a whole new world of technological possibilities employing nuclear energy, but demand for new, more effective weapons in a world at war shifted the focus onto the manufacture of weapons of mass destruction as its primary application. Once the international community acknowledged the destructive capabilities of nuclear weapons, their destiny was to become the subject of international debate. The nations that emerged as the dominant powers in the polarized world of the postwar period spearheaded the arms race, which was largely aimed at developing nuclear weapons. It is these historic tensions between the USSR and the United States that help shed light on Russia’s current foreign policy toward the United States on the subject of nuclear weapons.